2019
DOI: 10.1093/toxsci/kfz174
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Neuroimaging Markers Influenced by Lifetime Occupational Manganese Exposure

Abstract: Manganese (Mn) is a neurotoxicant that many workers are exposed to daily. There is limited knowledge about how changes in exposure levels impact measures in magnetic resonance imaging (MRI). We hypothesized that changes in Mn exposure would be reflected by changes in the MRI relaxation rate R1 and thalamic γ-aminobutyric acid (GABAThal). As part of a prospective cohort study, 17 welders were recruited and imaged on 2 separate occasions approximately 2 years apart. MRI relaxometry was used to assess changes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…In welders, thalamic GABA levels were found to be associated with Mn deposition and the rate of Mn exposure, being the highest values observed at high exposure with air Mn levels of 0.23 ± 0.18 mg/m 3 [ 184 ]. Specifically, thalamic GABA levels in welders significantly correlated with air Mn concentrations and cumulative exposure for the last three and 12 months [ 185 ]. However, another study did not observe any association between thalamic and striatal GABA levels and blood Mn or airborne metal exposure levels in welders [ 186 ].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…In welders, thalamic GABA levels were found to be associated with Mn deposition and the rate of Mn exposure, being the highest values observed at high exposure with air Mn levels of 0.23 ± 0.18 mg/m 3 [ 184 ]. Specifically, thalamic GABA levels in welders significantly correlated with air Mn concentrations and cumulative exposure for the last three and 12 months [ 185 ]. However, another study did not observe any association between thalamic and striatal GABA levels and blood Mn or airborne metal exposure levels in welders [ 186 ].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…We have shown that neurotransmitter concentration, specifically γ-aminobutyric acid (GABA), the primary inhibitory neurotransmitter in the central nervous system, is altered with Mn exposure. Specifically, GABA is higher in the thalamus in groups exposed to higher levels of Mn (Ma et al, 2018) and changes proportionately with levels of Mn exposure (Edmondson et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Thalamic GABA-Prior studies (Edmondson et al, 2019;Long et al, 2014;Ma et al, 2018) have shown that thalamic GABA (GABA Thal ) concentrations are correlated with Mn exposure. Therefore, we included GABA Thal as a target variable.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…На нашу думку, причина розбіжностей пов'язана з особливостями експонування. [11,[20][21][22]. Саме з функціональним дисбалансом медіаторних систем мозку пов'язують порушення секреції гормонів гіпофіза [23].…”
Section: аналіз літературних данихunclassified